An Improved System for Rapid in vitro Regeneration of Saintpaulia ionantha (Plant Tissue Culture and Biotechnology, 2014)
For rapid multiplication and genetic manipulation of African violets (Saintpaulia ionantha Wendl.) was aimed at developing a rapid and efficient regeneration and adaptation system from leaf explants. Using RM medium supplemented with different combinations of growth regulators, we developed a highly efficient and time-saving in vitro regeneration protocol. The developed system was also successfully applied for plant regeneration from petiole and internode explants of several Saintpaulia cultivars at a high efficiency. Regeneration occurred through both somatic embryogenesis and shoot organogenesis at a high frequency. Also, we developed a rapid root formation protocol followed by their efficient adaptation for in vitro regenerated plantlets. Plant Tissue Cult. & Biotech. 24(1): 37-45, 2014 (June) D. O. I. http://dx.doi.org/10.3329/ptcb.v24i1.19194